Concentration-Dependant Antioxidant Activity of Pentoxifylline in Nitrite-induced Hemoglobin Oxidation Model - Tavga A. Aziz (College of Pharmacy University of Baghdad, 2017)
Free radical formation in heme proteins is recognized as a factor in mediating the toxicity of many chemicals. The present study was designed to evaluate the dose-response relationship of the free radical scavenging properties of pentoxifylline in nitrite-induced Hb oxidation. Different concentrations of pentoxifylline were added at different time intervals of Hb oxidation in erythrocytes lysate, and formation of methemoglobin (MetHb) was monitored spectrophotometrically. The results showed that in this model, pentoxifylline successfully attenuates Hb oxidation after challenge with sodium nitrite; this protective effect was found to be not related to the catalytic stage of Hb oxidation, though such effect was reported to be more prominent when the compound was at the same time of induction of Hb oxidation with nitrite. In conclusion, pentoxifylline can effectively, in concentration-dependent pattern, attenuate sodium nitrite-induced Hb oxidation in vitro. Key words: pentoxifylline, radical scavenging, hemoglobin oxidation